Identification and characterization of NAGLU mutations in a Sanfilippo B syndrome patient with a novel genotype (p.Y140C/p.R297X) - Christensen, Chloe L.; Ashmead, Rhea E.; Choy, Francis Y.M. (Archives of Clinical and Biomedical Research, 2017)
Background: Sanfilippo B syndrome, or mucopolysaccharidosis type IIIB (MPS IIIB), is a rare lysosomal storage disorder resulting from mutations in NAGLU, which encodes for the enzyme α-Nacetylglucosaminidase (NAGLU). Patients afflicted with this disease experience mild somatic disease symptoms, but severe and ultimately lethal neurodegeneration. Patients often succumb to their symptoms in the first two decades of life. Sanfilippo B syndrome is a molecular heterogeneous disorder, in which nonsense and missense mutations frequently result in a genetic compound genotype, leading to the disease phenotype. Case Report: We report a novel compound heterozygous genotype (p.Y140C/p.R297X) in a Sanfilippo B patient. The level of NAGLU activity assayed from cultured skin fibroblasts was 0.6% of normal, confirming the biochemical diagnosis of Sanfilippo B syndrome. Immunoblot analysis using an anti- NAGLU antibody showed that the amount of NAGLU protein present was about 50% of normal. Conclusion: We have identified a novel genotype p.Y140C/p.R297X in a patient with Sanfilippo B syndrome that results in near zero NAGLU enzyme activity. We postulate that the nonsense mutation p.R297X produces either an unstable mRNA transcript or truncated protein that is rapidly degraded, whereas the missense mutation p.Y140C results in a stable but catalytically defective enzyme with near zero residual NAGLU activity. We conclude that the p.Y140C/p.R297X genotype is likely to result in a poor prognosis due to a detrimental biochemical phenotype.